math/calculus

posted by .

find f"(x) if f(x)= cube root(x^2-2x+1)

  • math/calculus -

    Note that x^2 - 2x + 1 = (x-1)^2
    f(x) = (x-1)^2/3
    f' = 2/3 (x-1)^-1/3
    f'' = -2/9 (x-1)^-4/3

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Algebra

    Could you please help me with some math problems?
  2. Calculus

    Find the functions a) f o g, b) g o f, c) f o f, d) g o g, and their domains. f(x)= square root of x, g(x)= cube root of 1-x These are my answers, but I am not sure about them and I only figured out one domain... that is the part that …
  3. Calculus

    Express the function in the form f o g. G(x)= The cube root of (x/1+x) So, (f 0 g)(x)= f(g(x))= f(cube root of x/1+x)= I don't know how to finish the problem because it does not give you the information for F(x)?
  4. Calc

    Find the functions a) f o g, b) g o f, c) f o f, d) g o g, and their domains. f(x)= square root of x, g(x)= cube root of 1-x These are my answers, but I am not sure about them and I only figured out one domain... that is the part that …
  5. AP Calculus

    If the linearization of y= cube root of x at x=64 is used to approximate cube root of 66, what is the percentage error?
  6. Algebra

    Simplify: 5(cube root of 16) + 2(cube root of 54) 5 times the cube root of 16 plus 2 times the cube root of 54. I do not know how to type in the radical signs. Sorry.
  7. Calculus-Solved-Please Check?

    estimate cube root of 25 by linear approximation f(x+delta(x))= f(x) + (df(x)/x) * deltax 3 + 1/3x^(-2/3) * -2 3 - 2/3x^(-2/3) 3 - (2/3* ((cube root(9))) is this right?
  8. Math

    Use differential, (i.e. linear approximation), to approximate cube root of 64.1 as follows: Let f(x) = cube root of x. The linear approximation to f(x) at x = 64 can be written in the form y = mx+b. Compute m and b and find cube root …
  9. Pre-Calculus 11

    What is the entire radial form of -3* cube root of 2?
  10. Calculus AB

    Please help me with this WS 1) Find the value of lim as x-->-(square root of 3) of (-x^4 + 5x^2 -6)/(x+(square root of 3) 2) Find the distance between the discontinuities of g(x)= ((square root of x-4))/(x^2 -5x -1) 3)Find the value …

More Similar Questions